2015
DOI: 10.1016/j.celrep.2015.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Off-Target V(D)J Recombination Drives Lymphomagenesis and Is Escalated by Loss of the Rag2 C Terminus

Abstract: SUMMARY Genome wide analysis of thymic lymphomas from Tp53−/− mice with wild-type or C-terminally truncated Rag2 revealed numerous off target, RAG-mediated DNA rearrangements. A significantly higher fraction of these errors mutated known and suspected oncogenes/tumor suppressor genes than did sporadic rearrangements (p<0.0001). This tractable mouse model recapitulates recent findings in human pre-B ALL and allows comparison of wild-type and mutant RAG2. Recurrent, RAG-mediated deletions affected Notch1, Pten, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 28 publications
3
37
0
Order By: Relevance
“…Destabilization of the postcleavage RAG complex and increased aberrant recombination product including chromosomal translocations involving VDJ loci were observed in mutants lacking the C‐terminal residues 352‐527 . Furthermore, p53‐deficient animals carrying a core RAG2 deletion have increased NHEJ activity associated with genomic instability and accelerated lymphomagenesis …”
Section: Structure Of the Human Rag 1 And Rag2 Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Destabilization of the postcleavage RAG complex and increased aberrant recombination product including chromosomal translocations involving VDJ loci were observed in mutants lacking the C‐terminal residues 352‐527 . Furthermore, p53‐deficient animals carrying a core RAG2 deletion have increased NHEJ activity associated with genomic instability and accelerated lymphomagenesis …”
Section: Structure Of the Human Rag 1 And Rag2 Proteinsmentioning
confidence: 99%
“…27,[32][33][34] Furthermore, p53-deficient animals carrying a core RAG2 deletion have increased NHEJ activity associated with genomic instability and accelerated lymphomagenesis. 34,35 The crystal and cryo-electron microscopy structures of RAG1/ RAG2 core proteins have revealed a Y-shaped structure, 23,36 with the RAG1 NBD dimer forming the stem of the Y, while additional regions along the central and C-terminal region of RAG1 act as DNAbinding surfaces for the RSS heptamer and coding flank. The three catalytic residues (D603, D711, and E965) reside in the RNH domain and together with the carboxy-terminal domain form the crevice of the Y structure.…”
Section: Phosphorylation Of Residue T490 By the Cyclin A-cdk2 Complexmentioning
confidence: 99%
“…For long, only few cRSS have been formally described outside V(D)J loci both in healthy individuals and in tumorigenic contexts (Lieber et al 2006; Schlissel et al 2006; Onozawa and Aplan 2012). More recently, high throughput techniques coupled with DNA break bait strategies identified hundreds of RAG “off-target” breaks all over the genome(Hu et al 2015), and targeted approaches in tumors identified frequent illegitimate recombination events in specific loci (Papaemmanuil et al 2014; Mijuskovic et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the absence of the RAG2 C-terminal region results in elevated RAG-mediated genome instability (25,59). These findings together are consistent with the idea that the secondary mode of RAG1 recruitment to H3K27Ac-rich regions of the genome is more likely to result in off target RAG activity than the primary, H3K4me3-driven mode of recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Though sites of RAG-mediated genomic instability tend to be enriched in cRSSs, the genome-wide distribution of off-target RAG activity is neither as frequent nor as uniform as the frequency and distribution of cRSSs would predict. Instead, illegitimate RAG-mediated events associated with leukemias and lymphomas are focused in active promoters and enhancers (25,26). Hence, prediction of RAG off-target activity requires an understanding of the mechanism by which RAG1 is targeted to specific places in chromatin, rather than merely predicting the location of cRSSs.…”
Section: Introductionmentioning
confidence: 99%